A traceable maturity assessment method based on enterprise architecture modelling - Vieira, R.; Cardoso, E.; Becker, C. (2014 IEEE 18th International Enterprise Distributed Object Computing Conference Workshops and Demonstrations, 2014)
Maturity assessments of business processes and capabilities are powerful tools for organizational improvement. Business process modelling is a key activity in the assessment of organizational maturity and capability of processes. However, the resulting models are complex and can often not be communicated successfully to the organizational stakeholders. Similarly, assessment methods rely strongly on the expertise of the assessors translating their perception of an organization into an assessment outcome. These assessments often carry a subjective component and are hard to compare. Moreover, they lack efficient traceability mechanisms as organizations evolve. Additionally, mainstream methods such as ISO 15504 and SCAMPI are complex, expensive and resource demanding, which place them out of reach for many organizations. This paper describes a research approach that builds on Enterprise Architecture models and IT Governance frameworks to guide the definition of a simple process metamodel for maturity assessment. This simple meta-model is used to create an intermediary representation that can be communicated to stakeholders. A formal expression of maturity conditions in SPARQL queries increases the objectivity of the assessment and separates it from the collected and formalized evidence. We discuss our model and method and report on a preliminary case study.